Correlates of anxiety and depression in a community cohort of people who smoke methamphetamine. (August 2022) - Duncan, Zoe; Kippen, Rebecca; Sutton, Keith; Ward, Bernadette; Agius, Paul A; Quinn, Brendan; Dietze, Paul
Objective: Anxiety and depression are the most common mental health disorders experienced by Australians. These disorders are commonly found in people who use methamphetamine; however, much of this research has involved participants recruited from treatment settings who inject methamphetamine. We therefore explored (1) the prevalence of moderate to severe anxiety and depression in a community-recruited cohort who smoked methamphetamine and (2) examined potential factors associated with moderate to severe anxiety or depression in this cohort. Method: Data were derived from baseline surveys of 725 participants of the prospective 'VMAX' study, recruited from metropolitan and non-metropolitan areas of Victoria, Australia, via snowball and respondent-driven sampling. Anxiety and depression were measured using the Generalized Anxiety Disorder-7 and the Patient Health Questionnaire-9 instruments. Independent associations between moderate to severe scores on these measures and demographic, socio-economic, substance use and other health and social characteristics were examined using multivariable logistic regression. Results: More than half (60%) of the participants were classified as experiencing moderate to severe anxiety and/or depression. In the multivariable models, having poor/very poor self-rated health, methamphetamine dependence and being unemployed were associated with higher odds of experiencing both moderate to severe depression and moderate to severe anxiety. Living in a large rural town, identifying as Aboriginal and Torres Strait Islander and smoking methamphetamine were associated with lower odds of experiencing moderate to severe depression. Being female was associated with higher odds of experiencing moderate to severe anxiety. Conclusion: The high rates of anxiety and/or depression found in the VMAX cohort were associated with demographic, socio-economic, substance use and other health and social factors. The prevalence of moderate to severe anxiety is a novel finding that warrants further study. Further work is needed to determine how anxiety and depression change over time among people who smoke methamphetamine, to help identify key intervention points.